Study of labetalol vs. methyldopa in treatment of pregnancy induced hypertension - Gurjar, Bhakti G.; Malewar, Samidha S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypertension is a common medical problem encountered during pregnancy and is associated with increased risk of adverse outcomes. Objective of this study was to compare efficacy and safety of Labetalol and Methyldopa in controlling blood pressure in patients with PIH and pre-eclampsia. Methods: A comparative, prospective observational, single centre study conducted from November 2015 to November 2017 in women with PIH at Indira Gandhi Government Medical College, Nagpur. Group A included 100 patients treated with Labetalol while Group B included 100 patients who were given Methyldopa. Response in lowering of BP was assessed over a period of 7 days. Results: Labetalol treated group of patients showed significant fall from 143.50±7.30mmHg/101.30±3.93 (sytolic/diastolic) on 1st day to 126.10±5.49 mmHg/87.40±5.62 mmHg (sytolic/diastolic) on day 7, while systolic/diastolic BP in methyldopa group on 1st day was 145.20±7.17 mmHg/101.60±4.20 mmHg which was reduced to 129.20±4.86 mmHg/90.50±3.30 mmHg on day 7. Author found that MAP in Labetalol group reduced from 115.226±4.17 mmHg to 100.17±4.43 mmHg on day 7 while in Methyldopa group had MAP on admission 115.99±4.38 mmHg and on day 7 it reduced to 103.27±2.99mmHg which is highly significant. Conclusions: Labetalol controls systolic and diastolic blood pressure more rapidly and effectively than Methyldopa. Safety profile and adverse effects of Labetalol and Methyldopa are similar to each other.